MOBILITAS SOSIAL EKONOMI MASYARAKAT TRANSMIGRAN (Studi: di Jorong Bukit Harapan (SP3) Nagari Tiumang Kecamatan Tiumang Kabupaten Dharmasraya) - Aryani, Mesi - (Pendidikan Sosiologi, 2014)
Thesis Programs Study Sociology at STKIP PGRI West Sumatra 2014. This research intent to describe about social mobility transmigrans society at Jorong Bukit Harapan (SP3), Nagari Tiumang, Kecamatan Tiumang, Kabupaten Dharmasraya. Theory that is used in this research is by using of evolutionary-fungsionalis theory that interposed by Talcott Parsons. This research constitute qualitative research by use of descriptive type. The result of the observation show that : (1) Social mobility forms on society transmigran is vertical mobility, in vertical social it happens on society transmigran is stirred social rising phenomenal of economics, education, home form, asset and transmigran society position, (2) Thruster factor from within society transmigran is have wish from that transmigrans society for changed and also indigene society role to transmigrans society by interlaces good relationship, (3) Thruster Factor from outside society transmigran is federal roles, local government and officer nagari.